KORELASI PENGUASAAN PENGETAHUAN LINGKUNGAN HIDUP DENGAN SIKAP PESERTA DIDIK TERHADAP PENGELOLAAN SAMPAH 3R DI SEKOLAH - Aulia Rahmi Cahyono; Najimatul Ilmiyah; Febrianawati Yusup (Bioilmi: Jurnal Pendidikan, 2023)
Indonesia does not yet have a proper waste management system to deal with the increasing amount and various types of waste. Waste management with 3R (Reduce, Reuse, Recycle) is currently considered the most effective way to deal with waste. Knowledge of 3R waste management has been included in the school curriculum in environmental education, which is one of the implementations of the Adiwiyata Program. This study aims to determine the level of environmental knowledge, determine student attitudes towards 3R waste management, and determine the relationship between the two. This research is a correlational study with a quantitative approach. 51 students were selected by cluster random sampling from 165 students in class VIII MTsN 10 Hulu Sungai Selatan. Instruments in the form of tests and questionnaires. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results showed that the average score of environmental knowledge was 78.28 which was included in the high category, the attitude of students in 3R waste management showed an average score of 71.69 in the good category, and the relationship between the two was 0.576 on the test. pearson correlation which means there is a moderate correlation with a positive relationship.